Analysis of the Effect of Solvability Ratio, Profitability, and Market Ratio on Share Prices of Pharmaceutical Sub Sector Companies Listed on Indonesia Stock Exchange (IDX) Period 2014-2018 - Jevellyn Masril; Martha Martha (Institut Bisnis dan Teknologi Pelita Indonesia, 2020)
This research aims to determine the effects of financial ratios to share prices in pharmaceutical sector companies in Indonesia. The dependent variable used was Share Prices, while the independent variable included EPS, DER, ROA and PER. The samples taken were the companies listed on the pharmaceutical sector of Indonesia Stock Exchange which were selected using purposive sampling. Among 12 companies listed on the pharmaceutical sector in the population, 3 companies have not published financial reports. Hence, the samples used in this research were only 9 companies. The method used was linear regression. The result showed that, earnings per share have positive influence to the share prices, debt to equity ratio have have negative influence to the share prices, return on assets have positive influence to the share prices and price earnings ratio have positive influence to the share prices.